Twelfth Five Year Plan (2012-17) and Annual Plan 2012-13 Volume II Uttar Pradesh - Planning Commission (Planning Commission, 2012)
Summary Statement of Major Headwise - Outlays and Expenditure Summary Statement of Sub-Major Headwise - Outlays and Expenditure Physical Targets & Achievements Externally Aided Projects - Outlays and Expenditure Externally Aided Projects - Physical Targets and Achievements Centrally Sponsored Schemes - Outlays and Expenditure Voluntary Sector - Outlays and Expenditure Women Component (WC) - Outlays and Expenditure Women Component (WC) - Physical Targets and Achievements Employment Generation (EMP-I) - Outlays and Expenditure
Government of Uttar Pradesh State Planning Commission